Pelatihan Penulisan tindakan kelas (PTK) untuk guru-guru SMK Al- HIKAM Geger (Eduscotech, 2023)
The demands of teacher professionalism in the Education 4.0 era require educators to act as agents of innovation and engage in continuous self-reflection through Classroom Action Research (CAR). CAR plays a crucial role in improving evidence-based learning quality and is a fundamental requirement for supporting career advancement, particularly within the teacher promotion system. Preliminary observations at SMK Al-HIKAM Geger revealed a significant gap: most teachers experienced difficulties throughout the CAR writing process, from identifying actionable classroom problems to structuring reports based on scientific standards. This challenge has contributed to teachers’ reluctance to apply for promotion, ultimately hindering pedagogical innovation in vocational education settings.This community service program aims to enhance teachers’ competence in systematically compiling and completing CAR reports in accordance with scientific principles. The training was implemented using an intensive two-day andragogical approach centered on practical workshops and supported by an ideal participant-to-facilitator mentoring ratio (10:3). The focus of the activity included personalized coaching to help teachers translate classroom issues into a scientific framework, covering stages such as problem identification, formulation of qualitative research questions, and mastery of data collection techniques.The program generated three expected outcomes: (1) measurable improvements in teachers’ understanding of CAR methodology based on post-test results; (2) the production of at least one implementable CAR proposal draft by each participant; and (3) the development of a sustainable culture of research and reflective practice within the school. In the long term, this program supports the realization of evidence-based learning innovation, improvement in vocational education quality, and increased teacher success in career advancement through scientific publication. This initiative serves as a strategic investment in strengthening professional teaching standards.